Pertanggungjawaban Hakim Penerima Suap: Studi Kasus Tiga Hakim PN Surabaya dalam Perkara Ronald Tannur - Mery Pemilia Astriyanti; Anza Ronaza Bangun (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2025)
This study aims to analyze the legal accountability of three judges of the Surabaya District Court who were proven to have been involved in bribery practices during the examination process of a case that resulted in the acquittal of Gregorius Ronald Tannur, the son of Edward Tannur, a former member of the Indonesian House of Representatives from the National Awakening Party (PKB). The study focuses on identifying the forms of legal responsibility that may be imposed on judges who receive bribes, as well as examining the abuse of judicial authority that influenced the issuance of the court decision. This research employs a normative juridical method using a statutory and case approach, through an analysis of Law Number 48 of 2009 on Judicial Power, Law Number 31 of 1999 in conjunction with Law Number 20 of 2001 on the Eradication of Corruption Crimes, Decision of the Surabaya District Court Number 454/Pid.B/2024/PN SBY, and the Joint Decree of the Supreme Court and the Judicial Commission of 2009 concerning the Code of Ethics and Guidelines for Judicial Conduct. The findings indicate that judges proven to have accepted bribes may be subject to criminal sanctions in the form of imprisonment and/or fines, ethical sanctions imposed by the Judicial Commission, as well as administrative sanctions in the form of dishonorable dismissal, and that court decisions rendered by judges involved in bribery may be challenged through available legal remedies. This study underscores the importance of strengthening internal and external oversight mechanisms and enhancing transparency in judicial proceedings to maintain and restore public trust in the judiciary.